The impact of social capital on international financial integration - Shad, Maryam; Ibrahim, Saifuzzaman; Wan Ngah, Wan Azman Saini; Baharumshah, Ahmad Zubaidi; Burhan @ Jaohari, Nik Ahmad Sufian (Faculty of Economics and Management, Universiti Putra Malaysia, 2018)
This study investigates the impact of social capital on international financial integration (IFI) using a newly constructed social capital series. Although previous studies have identified the social capital as one of the perquisites of IFI, the relationship between social capital and IFI is inconclusive. This study employs the generalized method of moment (GMM) panel technique on a sample of 60 countries for the period of 1990 to 2014. The results suggest that social capital can positively affect IFI, where improvement of social capital can promote international cooperation in financial market.